Analisis Faktor-Faktor yang Memengaruhi Purchase Intention terhadap Perusahaan Jasa Paket di Kota Batam - Kangnanda, Vanness; Nurjanah, Listia (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to analyze consumer preferences for parcel delivery services in Batam City, focusing on JNT Express, JNE, J&T Cargo, and SiCepat as the primary service choices. The research examines key factors influencing consumer decision-making and the impact of tax regulations on the distribution of goods from Batam. A quantitative method was employed by distributing an online questionnaire to 200 respondents who had used parcel delivery services and met the research criteria. The variables investigated include information, atmosphere, convenience, enjoyment, uncertainty, service, consumer attitude, and purchase intention, selected based on prior studies demonstrating their relevance in e-commerce and logistics contexts. The findings reveal that information, enjoyment, and service significantly influence consumer attitude, while atmosphere, convenience, and uncertainty show no significant effects. Consumer attitude is also proven to significantly affect purchase intention. SmartPLS analysis indicates that the data are free from Common Method Bias (CMB) and meet the required validity and reliability criteria, including outer loadings, AVE, Cronbach’s Alpha, and Composite Reliability. Despite a decline in parcel shipment volume from Batam over the past three years due to tax regulations, information availability and service quality remain the primary determinants of consumer purchase intention. These results highlight the need for delivery service providers to prioritize information accessibility, convenience, and service excellence to strengthen consumer attitudes and encourage purchase intention.